The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/pathogens9020144
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Acanthamoeba T5 from Water: Characterization of Its Pathogenic Potential, Including the Production of Extracellular Vesicles

Abstract: Acanthamoeba is a genus of free-living amoebae widely distributed in nature, associated with the development of encephalitis and keratitis. Despite the fact that it is common to find genotype T5 in environmental samples, only a few cases have been associated with clinical cases in humans. The wide distribution of Acanthamoeba, the characteristic of being amphizoic and the severity of the disease motivate researchers to focus on the isolation of these organisms, but also in demonstrating direct and indirect fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 65 publications
4
15
0
Order By: Relevance
“…The disappearance of a 47‐kDa band also indicated the existence of cysteine and metalloproteases in the EVs cargo. These findings corroborate previous studies that showed predominance of serine proteases and the presence in lower amount of metallo‐ and cysteine proteases in Acanthamoeba , either in conditioned medium (Alsam et al, 2005; Cirelli et al, 2020; Khan, 2006; Serrano‐Luna et al, 2006; Sissons et al 2005; Ramírez‐Rico et al, 2015), or in EVs (Gonçalves et al, 2018; Retana‐Moreira et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The disappearance of a 47‐kDa band also indicated the existence of cysteine and metalloproteases in the EVs cargo. These findings corroborate previous studies that showed predominance of serine proteases and the presence in lower amount of metallo‐ and cysteine proteases in Acanthamoeba , either in conditioned medium (Alsam et al, 2005; Cirelli et al, 2020; Khan, 2006; Serrano‐Luna et al, 2006; Sissons et al 2005; Ramírez‐Rico et al, 2015), or in EVs (Gonçalves et al, 2018; Retana‐Moreira et al, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…In the last years, studies have demonstrated the release of EVs by pathogenic protozoan and that these vesicles can act crucially in mechanisms of invasion and host immunomodulation (Mantel & Marti, 2014; Soares et al, 2017; Torrecilhas et al, 2012; Twu et al, 2013). EVs are also released by Acanthamoeba trophozoites and their possible involvement with contact‐independent mechanism of pathogenicity was recently shown (Gonçalves et al, 2018; Lin et al, 2019; Retana‐Moreira et al, 2020).…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations